Mechanism of Yiqi Huoxue Granule in promoting angiogenesis of skin lesion tissue by increasing CSF2 to reduce mesenchymal stem cell apoptosis - Shi, Weili; Wang, Shuhui; Liu, Shanshan; Lei, Zhen; Yan, Peishuo; Wang, Xinzhou; Lu, Chaoqun; Qin, Nan; Lu, Pengfei (Frontiers in Pharmacology, 2026)
ObjectiveTo explore the effect and mechanism of the Yiqi Huoxue Granule in improving the survival of mesenchymal stem cells (MSCs) induced by hypoxia and promoting angiogenesis in damaged tissues.MethodsAnimal experiments: A rat skin injury model was established. The skin healing degrees were compared among the model group, MSC group, and Yiqi Huoxue Granule group and Yiqi Huoxue Granule combined with MSC group. The intensity of DIR-labeled MSCs was observed by frozen section, and the expression of CD31 in tissues was detected by immunofluorescence. Cell experiments: A hypoxic MSC model was constructed. The effect of the Yiqi Huoxue Granule on the viability of hypoxic MSCs was detected by CCK8. Flow cytometry was used to observe the apoptosis rate of MSCs. The effect of Yiqi Huoxue Granule on tube formation of MSCs was observed by tube formation assay. Differentially expressed genes were analyzed using transcriptomics and verified through RT-PCR. Key factors were analyzed by PPI.ResultsDIR-labeled MSCs showed that at a concentration of 50 μM, the count of red spots in MSCs significantly increased compared to 12.5 μM and 25 μM (P < 0.01 or 0.001), and there was no statistical difference in cell viability compared to the 12.5 μM and 25 μM groups (P > 0.05), thus 50 μM DIR was selected for in vivo tracing. On the 11th day of intervention, compared to the model group, MSC group, and Yiqi Huoxue Granule alone group, the wound diameter in the Yiqi Huoxue Granule combined with MSC group was significantly reduced (P < 0.05). On the 7th day of intervention, the percentage of CD31 fluorescence area in the Yiqi Huoxue Granule combined with MSC group was significantly increased compared to the MSC group (P < 0.01), and compared to the MSC group, the MSC combined with Yiqi Huoxue Granule increased the MSC DIR fluorescence area and intensity (P < 0.05). Cell experiment results showed that compared to the hypoxic model group, high-dose Yiqi Huoxue Granule reduced MSC apoptosis (P < 0.001) and promoted lumen formation. Transcriptomic analysis identified 19 apoptosis-related genes linked to hypoxia. Following RT-PCR and PPI analysis, 9 genes centered around Csf2 were selected. Among these, Csf2, Il1a, Il6, Fgf10, and Cd274 were found to be upregulated, while Ccl2, Pde1a, Nptx1, and Igfbp3 were downregulated.ConclusionThis research offers a novel perspective for MSC apoptosis using Yiqi Huoxue Granule. Yiqi Huoxue Granule promotes the survival of MSCs under hypoxia and in damaged skin tissue, improves angiogenesis in damaged skin tissue, accelerates skin wound healing, and is closely related to the elevation of Csf2.